Der Prophet Haggai in der bildenden Kunst: Vor allem ein Weihnachtsbote (Teil 2) - Koenen, Klaus (Die Bibel in der Kunst, 2025)
Historically, Haggai is credited with having promoted the building of the Second Temple in 520 BC.However, in order to understand his reception in visual arts, the allegorical interpretation, dating back to the Early Church, is much more important than the historical reading. It links a number of verses in the Book of Haggai to the New Testament. Hag 2:8 (Vulg.), for example, is understood as an announcement of the coming of the Desired One, which is taken to be Christ and thus referring to Christmas. This is the announcement of Haggai which is most frequently received in visual arts. The announcement of a cosmic earthquake in Hag 2:7,22 (Vulg.) is understood as an announcement of the earthquake at the death of Jesus (cf. Mt 27,51). Since allegorical interpretations like those are widely documented in connection with depictions of Haggai, depictions of the prophet without epigraphs perhaps are to be interpreted in the same way. Furthermore, images that show Haggai calling for the Temple to be rebuilt may, in fact, have the building of the Christian Church in mind.